2016
DOI: 10.1007/s11695-016-2383-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intragastric Balloon Before Laparoscopic Gastric Bypass on Patients with Super Obesity: a Randomized Multicenter Study

Abstract: IGB insertion before LGBP induced weight loss but did not improve the perioperative outcomes or affect postoperative weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
1
22
1
2
Order By: Relevance
“…Abstracts from the remaining articles where evaluated, leaving 25 full articles concerning weight loss prior surgery. After reading the full text, we concluded that only 7 out of 25 papers focused on the effects of weight loss prior to BS [13][14][15][16][17][18][19], and only 3 of them were randomized control trials specifically comparing patients who achieved a significant weight loss before surgery with patients who did not [13][14][15]. The characteristics of the three trials are reported in Table 1.…”
Section: Controversies About Pre-operative Weight Lossmentioning
confidence: 99%
“…Abstracts from the remaining articles where evaluated, leaving 25 full articles concerning weight loss prior surgery. After reading the full text, we concluded that only 7 out of 25 papers focused on the effects of weight loss prior to BS [13][14][15][16][17][18][19], and only 3 of them were randomized control trials specifically comparing patients who achieved a significant weight loss before surgery with patients who did not [13][14][15]. The characteristics of the three trials are reported in Table 1.…”
Section: Controversies About Pre-operative Weight Lossmentioning
confidence: 99%
“…Air and fluid filled intra-gastric balloons (IGB) have also been tried to achieve weight loss in the super-obese patients. In a randomised multicentre trial of 115 patients, 55 patients with a BMI of 54 kg/m 2 had IGB inserted for 6 months which led to a BMI loss of 2.8 kg/m 2 but this did not improve the peri-operative outcomes after laparoscopic gastric bypass [ 23 ]. This magnitude of weight loss could be achieved with diet, behaviour and exercise regimes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intragastric balloons ( Figure 2) have been thought to provide a potential bridge to bypass surgery in super-obese patients (body mass index >50 kg/m 2 ). In a prospective randomized trial of 115 super-obese patients, 82 55 received intragastric balloons and 60 received standard medical care. Although weight loss was substantial with intragastric balloon, there was no effect on perioperative outcomes.…”
Section: Endoscopic Bariatric Proceduresmentioning
confidence: 99%